Development of live worksheets assisted diagnostic assessment instruments to measure understanding of science concepts prospective elementary school teachers - Hasnawati Hasnawati; Muhammad Syazali; Arif Widodo (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
Understanding the material's content is one of the main competencies a teacher must possess, so it is necessary to diagnose the extent of understanding the level of understanding of science concepts for prospective teachers. This study aims to produce a valid and practical diagnostic assessment instrument assisted by live worksheets to measure the level of understanding of science concepts for elementary school teacher candidates. This research is development research using a 4-D model (define, design, develop and disseminate). In the define stage, science concepts that are difficult to understand for prospective elementary school teacher students have been identified, namely the material of temperature and heat, electricity, magnetic fields, and the solar system. The next stage is to design the right instrument to diagnose the level of understanding of science concepts for elementary school teacher candidates, namely a diagnostic instrument with three-level multiple choice questions integrated into the live worksheet application. Furthermore, in the development stage, the questions pay attention to the final abilities expected to be achieved in students based on the semester learning plans for special science education courses on materials identified at an early stage. The instrument that has been developed is then tested for validity and practicality. The validity test results obtained an average score of 3.8 which means the instrument is very valid, and the results of the practicality test show a practical instrument with an average score of 3.5. The final stage of this research is dissemination, namely the process of disseminating research and development products in the form of diagnostic assessment instruments assisted by live worksheets to measure the level of understanding of the science concepts of elementary school teacher candidates that have been developed. In conclusion, the live worksheet-assisted diagnostic assessment instrument developed is valid and practical for measuring the level of understanding of elementary school teacher candidates.